Coupling analysis of contra-rotating fan interstage pressure pulsation and blade vibration based on wavelet reconstruction. - Xinzhe Zhang; Chen Dai; Zunlong Jin; Sławomir Dykas; Guojie Zhang (PLoS ONE, 2021)
In recent years, the flow characteristics research of the interstage region in counter-rotating axial fans in terms of fluid dynamics has attracted much attention. Especially, the dynamic relationship between interstage pressure pulsation and blade vibration in counter-rotating axial fans has not yet been clarified. This paper performs the signal processing method of wavelet decomposition and reconstruction in time-frequency analysis process. Under different flow conditions, weak-coupling numerical simulation program is employed to analyze the fluid-structure coupling interaction between interstage pressure pulsations and blade vibrations in counter-rotating axial fans. The results indicate that the fluid-structure coupling interaction field in the interstage of counter-rotating axial fans mainly excites the first-order vibration of the second-stage blade. At the same time, the consistency between the pulsation frequency and the vibration frequency of the airflow reflects the good coupling property. Two stage blades cut the airflow to cause field changes and airflow pulsation, and then, airflow pulsation causes blades deformation and produces vibrations of the same frequency at the blade. The deformation of the blades, in turn, causes the flow field changes. Rotating stall, vortex movement and breakdown produced low-frequency airflow pulsation and vortex vibration of the blade.